INCIDENCE OF FRUIT FLY, Anastrepha fraterculus (DIPTERA: TEPHRITIDAE), IN CULTIVARS OF PLUM UNDER ORGANIC SYSTEM - Gonçalves, Paulo Antonio de Souza; Debarba, João Favorito; Keske, Cláudio (Revista de Ciências Agroveterinárias, 2005)
The objective of this work was to evaluate the damage caused by fruit fly, Anastrepha fraterculus, in plum grown using the organic system. The field research was carried out in Ituporanga, SC, Brazil, during three consecutive growing seasons. The cultivars evaluated were Irati, Centenaria, Rosa Mineira, Januaria, Pluma 7, Reubenel, Carazinho and Santa Rosa Polirosa. All cultivars presented high damage caused by fruit fly. However, in the cultivar Irati, which is harvested until the middle of December, the damage was smaller. The results reported herein suggest that it is important to create other management strategies, in addition to the right cultivar choice, so that this insect can be properly controlled.